HUBUNGAN PELATIHAN BERCERITA TERHADAP KEMAMPUAN GURU DALAM BERCERITA DI TAMAN KANAK-KANAK - Rahmah Rahmah (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2016)
The purpose of this research is to discover the correlation of story telling training with the teacher’s story telling skill in Kindergarten. Applying quantitative paradigm, this research used the 37 teachers of the Kindergartens in Simpang Tiga Subdistrict, Pekanbaru, as the subjects. The data were collected by distributing questionnairer. The results showed, t counted was higher than t table, so Ho was rejected meaning that there is a significant correlation between story telling training with the teacher’s story telling skill in Kindergartens in Simpang Tiga Sub-district, Pekanbaru. Then the result of reliability test of each variable showed variable X (story telling training) is higher indicating all data analyzed with Alpha method was reliable. The result for variable Y (teacher’s story telling skill) was higher indicating all data analyzed with Alpha method was reliable.